The Use of Language Functions in Developing Ict-Based English Learning Material for Nurses - I Putu Agus Endra Susanta; I Nengah Sudipa; Ketut Artawa; I Wayan Simpen (International Journal of English and Applied Linguistics (IJEAL), 2024)
The purposes of this study are to (1) describe the realization of the use of teaching materials in learning English for nursing, (2) develop ICT-based English learning materials by using language functions needed in the field of nursing, (3) analyze the quality of ICT-based English learning materials developed by using language functions in the field of nursing. This research was conducted using an exploratory mixed-method design (Creswell, 2003). The results of this study show that; 1) The reality of English learning material did not yet fulfil the need of nursing students to master English for nursing seen in terms of input, content, language focus, and tasks, 2) the design of teaching materials for English speaking skills in the field of nursing with the use of language functions was developed into fifteen topics. The result of the development of this teaching material is in the form of teaching material products that are expected to be able to represent communicative abilities and help students and teachers to be able to achieve learning goals, 3) The quality of English teaching materials in the field of nursing with the use of English functions was classified as "excellent" to be implemented in organizing the teaching and learning process as evidenced by the results of the t-test, which was 0.002 (0.002<0.005). The results of the research and the findings of this study are suggested to be used as a reference source for other similar research and the product can be implemented in English language learning at vocational universities that focus on the field of nursing.